Current trends and challenges in EEG research on meditation and mindfulness - Paul Barrows; William Van Gordon; Paul Gilbert (Discover Psychology, 2024)
Abstract During the last four decades there has been a significant growth of interest in mindfulness-based practices and their potential to foster improvements in health, wellbeing and human functioning in a variety of clinical and nonclinical populations. With this growth has come a renewed interest in understanding the psychological processes involved as well as the neuropsychological mechanisms by which such practices operate and effect transformative personal experiences and positive change. The current perspective paper (i) presents a basic taxonomy of meditation types and the structure and function of the processes believed to be involved, (ii) describes these components in terms of key neuroanatomical regions of interest, and (iii) critically appraises current findings regarding EEG measures as they relate to different aspects of meditation, functional activity and connectivity across regions of interest. The correlates between mindfulness and EEG are well described in terms of attentional and interoceptive processes and neuroanatomical regions of interest. To a lesser extent, there is also a growing understanding of such correlates for meditation techniques centred on compassion and loving-kindness meditation. However, the same does not apply to wisdom-based and null-state meditation practices where consistent associations between neuropsychological processes and EEG characteristics have proven elusive. These latter practices are viewed by many as key to fostering the deeper transformative experiences underlying psychological and spiritual development, and although studies of null-state meditation have yielded promising theoretical developments, more research is required. Future research could also benefit from better standardisation of EEG measures and analytic techniques to allow more robust metanalyses, and greater consistency of terminology regarding the fundamental components of meditation practice.